An overview of the angular geomorphic lock – an anti-rutting model for sustainable road infrastructure - Christopher Nondo; Chewe Kambole; Yohane Tembo (Journal of Construction Project Management and Innovation)
Sustainable road infrastructure is largely dependent on the resilience of the road foundation to withstand dynamic stresses. From Empirical to Mechanistic Empirical Pavement Design Guidelines (MEPDG), the use of unbound granular materials (UGMs) has been specified for road foundation bases for flexible roads. Rutting is a common road failure from these designs. MEPDG includes climate change factors that essentially invalidate the empirical approach. However, both design approaches still rely on the anisotropic particle interlock of UGM upon compaction, notwithstanding traditional or intelligent compaction technology. The anisotropic character of compacted UGM only exhibits vertical stiffness with the highest shear stress located in the mid layer. This makes the interface between the surface of the compacted subgrade and the bottom of the compacted subbase incompatible. Consequently, the stiffness of the UGM is satisfactory for static loads, but when these become dynamic, the inter-granular transmission of these stresses creates a new challenge, non-linearity of stress and the ensuing propensity for stress rotation. A model subbase of a road foundation was modified acknowledging the natural angle of repose of UGM. The ribbed saw tooth structure with an inherent composite anisotropic character seemed to offer significant stiffness. A three-point shear stress localisation (3-PSSL) was experimentally created with three stress levels identified within the subbase and a fourth stress level in the base. This geomorphic lock is possible by the use of an angular geo-lock compactor (AGL). Added stiffness in the road foundation should avert rutting, thereby increasing resilience and sustainability of road infrastructure, and ultimately stimulating socio-economic development. World Intellectual Property Organisation (WIPO) has documented this ongoing research as patent No. WO 2021/048590 A1 awaiting entry into The National Phase. This is Work in Progress, where particle intra-lock may invalidate particle interlock.